Effect of 3 different applications of kinesio taping Denko® on electromyographic activity: Inhibition or facilitation of the quadriceps of males during squat exercise - Serrao, J. C.; Mezencio, B.; Claudino, J. G.; Soncin, R.; Sampaio Miyashiro, P. L.; Sousa, E. P.; Borges, E.; Zanetti, V.; Phillip, I.; Mochizuki, L.; Amadio, A. C. (Journal of Sports Science & Medicine, 2016)
Kinesio taping consists of a technique which uses the application of an elastic adhesive tape. It has become a widely used rehabilitation modality for the prevention and treatment of musculoskeletal disorders. The objective of this study was to verify the effect of the application of Kinesio Taping Denko® in three conditions (facilitation, inhibition, and placebo) on the electromyographic activity of the quadriceps and hamstrings muscles on facilitating or inhibiting the muscle function and on the perceived exertion during the barbell back squat exercise in healthy male subjects. Methods: It was a randomized, single-blinded and controlled study in which 18 males (28.0 ± 6.7 years old; 85.8 ± 8.2 kg mass; 1.80 ± 0.07 m tall; 0.97 ± 0.04 m lower limb length) performed barbell back squat exercise with different conditions of Kinesio Taping Denko® applications: Facilitation, inhibition and placebo. Previous to the mentioned conditions, all individuals were assessed without applying kinesio Taping Denko® during the exercise. OMNI scale was used after each set for perceived exertion evaluation. No differences (p < 0.05) in the electromyographic activity of the biceps femoris, vastus lateralis and vastus medialis or OMNI scale were recorded under any conditions. The results show that the kinesio taping denko®may not alter the magnitude of the electromyography activity of vastus lateralis, vastus medialis, and biceps femoris during the squat exercise. Furthermore, the perceived exertion was not affected by the kinesio taping denko® application.